Ethnoveterinary study of galactogenic recipes used by ruminant breeders to improve milk production of local cows in Benin Republic - Agani Agani, Zenabou; POMALEGNI, S. CHARLES .B.; AKOUEDEGNI, COOVI GUENOLE; BOKO, KADOÉITO CYRILLE; Bello Orou, Daouda; DOSSOU, JOSEPH; BABATOUNDE, SÉVÉRIN (My University, 2022)
Ethnopharmacological relevance: In Benin, traditional recipes are used to improve livestock dairy performance, but they are not sufficient documented. The study aimed to inventory the galactogenic recipes used by herders to improve production in cow farming. Aim of the study: The study aimed to inventory the galactogenic recipes used by herders to improve production in cow farming. Material and methods: We conducted semi-structured interviews among 65 peuls camps, 4 bioclimatic zones, and 565 farmers dialogue partners, including agro-pastoralist, healers and pastoralists from the rainy season April and May 2019. Detailed information about homemade herbal remedies of galactogenic recipes (plant species, plant part, manufacturing process) and the corresponding use reports (dialogue partner, category of use and route of administration) was collected. Then other to classify the various recipes identified into homogeneneous groups according to their effectiveness in stimulating milk, a numerical classification was carried out on the recipes taking into account the milk gain. Results: They showed that Peuls and Gandos sociocultural groups have a better knowledge of galactogenic recipes. Of the 295 recipes inventoried, 102 frequently cited recipes were divided into two groups. Group 2, consisting of 16 recipes, had a significantly (p < 0.001) higher milk yield than group 1. Vigna unguiculata (L.) Walp. and Arachis hypogaea L. were the main ingredients of the recipes (respectively 56 and 31% of incorporation rate). The composition of the recipes varied according to the agro-ecological zones. Herders in Northern Benin used more recipes based on Bobgunnia madagascariensis (Harms) J.H.Kirkbr. & Wiersema, Saba comorensis (Bojer ex A. DC.) Pichon and Euphorbia balsamifera Aiton. Those in Southern Benin mainly used recipes based on Gardenia aqualla associated with Vigna unguiculata (L.) Walp or Arachis hypogaea L.. To improve the effectiveness of galactogenic recipes, socio-cultural and magical-religious practices are used when procuring the plant material to be used, preparing the galactogen and administering the recipe to the animals. These include pronounced incantations or recited Koranic verses. The most commonly used route of administration is the oral route with an average treatment duration not exceeding 5 days. Conclusion: The study reveals that the majority of breeders (90%) opt for the use of galactogenic plants rather than synthetic products to improve milk production.
Keywords: Homemade recipes; Preparation; Milk yield; Breeders; Benin